Who indoor air quality guidelines : household fuel combustion. (World Health Organization, 2015)
Given the mixed history of success with past intervention projects and programmes and the fact that the 2.8 billion people still relying on traditional solid fuels are the world's poorest 40% it is clear that securing a rapid transition to clean efficient and modern household energy systems for cooking heating lighting and other household uses will be challenging. The overall objective of these guidelines is to inform and support governments and their implementing partners to bring about this transition as quickly and equitably as is feasible. The guidelines focus on the following.